The demands of training and match-play on elite and highly trained junior tennis players: A systematic review - Fleming, J. A.; Field, A.; Lui, S.; Naughton, R. J.; Harper, L. D. (International Journal of Sports Science & Coaching, 2023)
Objective Talented junior tennis players are exposed to high training loads and congested competition schedules. Understanding the demands of training and competition is important to prescribe training and recovery programmes that optimise performance. The purpose of this study was to systematically review and appraise the literature available on training and match-play demands in an elite and highly trained junior tennis population to inform practice and future research opportunities.